Voluntary tax compliance behavior of individual taxpayers in Pakistan - Ibn e Hassan; Ahmed Naeem; Sidra Gulzar (Financial Innovation, 2021)
Governments settle their financial obligations and pay for the public expenditures largely through finances generated from taxes. For many developing countries like Pakistan, the state authorities are still having difficulty to achieve tax compliance. Existing literature has yet to traverse individual's tax compliance behavior on developing countries. The current study, however, explores the relationships among voluntary tax compliance behavior of individual taxpayers with selected economic, social, behavioral and institutional factors. This individual tax compliance behavior is studied through the multi-perspective lenses of the theory of attribution, equity theory, expected utility theory, and social exchange theory. Quantitative design using the survey method was employed to collect data from 435 individual taxpayers through questionnaire. For testing linkage between constructs, through mediation and moderation tests, structural equation modeling technique was used. The results suggest that tax compliance simplicity has a larger impact on tax filing than perception about Government Spending and tax morale. Furthermore, perception of fairness significantly mediates the strengths between morale, simplicity, government spending and compliance behavior.
Keywords: 650; Compliance behavior; Individual taxpayers; Pakistan; Perception of fairness; Tax compliance simplicity; Tax morale; Voluntary tax